Aggression and bullying: a literature review examining their relationship and effective anti-bullying practice in schools - Kaliampos, George; Katsigiannis, Kostas; Fantzikou, Xrysoula (Universitas Majalengka, 2022)
Power relationships exists among students in schools which are often characterized by violent and aggressive behaviors. The current study deals with the concept of bullying. In particular, through literature review methodology, it aspires to answer into the following two research questions; ‘what is the evidence for a relationship between aggression and bullying’ and ‘what can be done in order to deal effectively with bullying in schools. Regarding the first research question, there seems to be a close connection between aggression and bullying. Indeed, both proactive and reactive aggression can be found in bullying. Nevertheless, it is stated that while aggression is a normal feeling which should not be suppressed, bullying is socially unacceptable. It can causes hurt to the victim and therefore it must be contemned in the most explicitly way. As for the second research question, whole school policies which take into account the social nature of bullying should be adopted by educators. Moreover, peer mediation schemes are discussed and a balance argument is given for them.